2022
DOI: 10.1177/02692155221107739
|View full text |Cite
|
Sign up to set email alerts
|

Can a new ward environment and intensive allied health staffing model enhance therapeutic opportunities in trauma care? A behavioural mapping study of patients’ activities and interactions

Abstract: Objective The aim of this study was to assess changes in patient activities and interactions observed in response to a new trauma ward at a level 1 trauma centre, and subsequently, a new allied health staffing model. Design Explorative case study using behavioural mapping. Setting Level 1 trauma centre in Melbourne, Australia. Participants Hospitalised trauma patients. Main measures Behavioural mapping of patients’ activities and interactions was conducted by two observers over three 4-day observation phases: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…A behavioral mapping study showed that the new ward environment was associated with increases in activities of daily living by patients, addition of the AHMOC to the new ward was associated with a 4-fold increase in gym usage and a 9-fold increase in interaction with allied health clinicians. 24 The findings of this study support the benefit of the new AHMOC on outcomes and costs of major trauma patients. Nevertheless, there were limitations to the study which warrant acknowledgement.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A behavioral mapping study showed that the new ward environment was associated with increases in activities of daily living by patients, addition of the AHMOC to the new ward was associated with a 4-fold increase in gym usage and a 9-fold increase in interaction with allied health clinicians. 24 The findings of this study support the benefit of the new AHMOC on outcomes and costs of major trauma patients. Nevertheless, there were limitations to the study which warrant acknowledgement.…”
Section: Discussionsupporting
confidence: 73%
“…The new ward alone was not associated with improvement in any of the outcomes of interest in this study. A behavioral mapping study showed that the new ward environment was associated with increases in activities of daily living by patients, addition of the AHMOC to the new ward was associated with a 4-fold increase in gym usage and a 9-fold increase in interaction with allied health clinicians 24 …”
Section: Discussionmentioning
confidence: 99%
“… 18 The broad nature of the facilitative environment is illustrated by the essential features of stroke unit care: 69 , 70 Structured assessment procedures Policies on early stages of management of common problems Policy on the ongoing rehabilitation Expertise in stroke management and rehabilitation with regular team education Multidisciplinary teamwork with regular planned team meetings Involvement of patients and families Other studies have shown that: Planned changes in the physical environment alter the behaviour of patients, increasing their activities. 71 74 Social factors influence adaptation; for example, after a stroke, community activity is influenced by social networks 75 and being with other people is associated with more movement of the affected arm. 76 The harm caused by inappropriate environments is also clear.…”
Section: Discussionmentioning
confidence: 99%
“…Planned changes in the physical environment alter the behaviour of patients, increasing their activities. 71 74 …”
Section: Discussionmentioning
confidence: 99%